Spontaneous Growth of 3D Silver Mesoflowers on Poly(4‐vinylpyridine) Brushes‐Grafted‐Graphene Oxide Films and Facile Creation of Nanoporosities over their Surface. Issue 71 (21st November 2019) - Feng, Lihua; Wang, Wenqin; Li, Xiyong; Chen, Tao
Abstract: Fabricating three‐dimensional (3D) hierarchical noble‐metal particles by spontaneous redox reactions between graphene and noble‐metal salts still remains a great challenge. Herein, the fact that graphene oxide (GO) itself acts as both a platform for grafting polymer brushes and a reducing agent to reduce [Ag(NH3 )2 ] + ions is taken advantages of. 3D flower‐like Ag mesoparticles (Ag mesoflowers, Ag MFs) with tunable size and shapes can spontaneous grow on poly(4‐vinylpyridine) brushes‐grafted‐graphene oxide (P4VP‐g‐GO) films in Ag(NH3 )2 OH solution without the use of any additional reducing agent. The residual Ag(NH3 )2 OH on 3D Ag MFs surface can be further reduced by NaBH4, causing abundant nanoporosities over the entire Ag MFs. The resulting Ag nanoporous MFs (Ag NMFs) with larger surface‐to‐volume ratio and higher nanoscale roughness exhibit ultrasensitivity in surface‐enhanced Raman spectroscopy (SERS) detection, and the detection limit for 4‐aminothiophenol is as low as 10 −13 m . Abstract : Sensing with flowers : 3D Ag mesoflowers (Ag MFs) with tunable size and shapes are spontaneously grown on poly(4‐vinylpyridine) brushes‐grafted‐graphene oxide (P4VP‐g‐GO) films in Ag(NH3 )2 OH solution without the use of any additional reducing agent (see scheme). The obtained Ag MFs could be facilely converted into Ag nanoporous MFs (Ag NMFs) with ultrasensitivity in surface‐enhanced Raman spectroscopy (SERS) detection.